E-Commerce System as A Web-Based Marketing Media for Fishermen's Catch in Wainami Village, Nabire Regency - Nicodemus Rahanra (Pt. Anagata Sembagi Education, 2025)
Weinami Village is a village located on an island adjacent to Napan Village. The livelihoods of the residents in the village are as fishermen. The geographical position of the research location which is far from the city center makes it difficult for fishermen to market their catch. The livelihoods of residents around Weinami Village are fishermen, therefore there are no buying and selling transactions in the village, so the fishermen are confused about distributing their catch. E-Commerce is a system that connects sellers and buyers in an interaction network. If analogized as a market, then the transactions that occur take place digitally, not in a physical location. In this case, the business center is not a real building, but a digital-based system. By utilizing the internet network, the process of marketing and selling catches can be carried out widely without being hindered by national borders (Apridiansyah.et.all.2019). The author has developed a web-based fishing catch marketing system, starting from application planning to database creation. In the process, there was an error in the code that caused an error, but it was finally fixed. Currently, the marketing system in Weinami Village has been connected via localhost for testing purposes. Furthermore, this system is planned to be further developed with its own domain so that it can be used by fishermen in Weinami Village, thus facilitating transactions between sellers and buyers